Synthesis and characterization of surfmers for the synthesis of polystyrene-clay nanocomposites - Samakande, Austin (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2005.